2013
DOI: 10.1038/ajg.2013.354
|View full text |Cite|
|
Sign up to set email alerts
|

EMerging BiomARKers in Inflammatory Bowel Disease (EMBARK) Study Identifies Fecal Calprotectin, Serum MMP9, and Serum IL-22 as a Novel Combination of Biomarkers for Crohn's Disease Activity: Role of Cross-Sectional Imaging

Abstract: Incorporation of both ICO and CTE into a single measure increased biomarker performance in CD. Combinations of fecal calprotectin and serum MMP9 for UC, and combinations of fecal calprotectin, serum MMP9, and serum interleukin-22 in CD, demonstrated the strongest association with imaging/endoscopy-defined inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 44 publications
2
68
0
1
Order By: Relevance
“…This led to the suggestion that the milder phenotype might be the result of growth hormone deficiency. However, the patient described by Dr. Castro-Gago and the two unusual patients we reported recently [4,5] have normal growth. Furthermore, these three patients who have in common the lack of muscle dystrophin carry different nonsense mutations.…”
mentioning
confidence: 69%
“…This led to the suggestion that the milder phenotype might be the result of growth hormone deficiency. However, the patient described by Dr. Castro-Gago and the two unusual patients we reported recently [4,5] have normal growth. Furthermore, these three patients who have in common the lack of muscle dystrophin carry different nonsense mutations.…”
mentioning
confidence: 69%
“…We also observe that MMP-9 levels may increase after discontinuing corticosteroid treatment. In support of this, it is reported in the literature that in several diseases such as Crohn's disease, asthma (in children) and rheumatoid arthritis, treatment with corticosteroids causes a decrease in circulating MMP-9 levels or in MMP-9 gene expression [2][3][4]. It has also been shown that blood MMP-9 levels are not influenced by prednisolone in patients affected by Takayasu arteritis [5].…”
mentioning
confidence: 79%
“…In quite a number of cases LVHT occurs familially [4]. Did any of the relatives, in particular the mother, father, or grandparents undergo echocardiography or cardiac MRI to find out if LVHT was familial and transmitted from the mother's or father's side?…”
Section: Plec1 Mutation Associated With Left Ventricular Hypertrabecumentioning
confidence: 99%
“…A further prospective study of 32 patients has validated its usefulness in predicting the rate of re-operation [31]. Faubion et al combined endoscopic evaluation with CTE assessment of CD severity in a manner similar to the simple endoscopic score for Crohn's disease (SES-CD) and found that the addition of CTE information correlated much better with biomarkers of inflammation than ileocolonoscopy alone [3]. For a simple CTE scoring system to be widely utilized clinically, the relationship of the CTE score to validated ileoscopic and MRI indices will need to be better understood, and the CTE index will need to convey both severity of disease in an individual segment as well as overall disease burden.…”
Section: Computed Tomography Enterographymentioning
confidence: 97%
“…As a disease process, the protean symptoms of CD are often non-specific such as abdominal pain and diarrhea [1]. Even validated clinical indices of CD severity, such as the Crohn's Disease Index of Activity (CDAI), the clinical endpoint for most therapeutic trials in CD, show poor correlation with biologic activity, especially in certain populations such as patients with fistulizing or obstructing disease [2][3][4]. In addition, there is little clinical suspicion of Crohn's fistulae and strictures in a substantial proportion of patients with these complications [5,6].…”
mentioning
confidence: 99%